(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the urgency of preserving the national musical heritage and the social significance of the masterpieces of national musical art in shaping the upbringing of the younger generation and nurturing them as well-rounded individuals. National music is considered not merely an aesthetic phenomenon but a crucial socio-cultural element in both society and human education. Particular attention is paid to the preservation and transmission of the art of maqom, its performing traditions, stylistic schools, and the teacher-student model to future generations in their authentic form. A value-based approach to national music is emphasized as an essential factor in developing young people’s spiritual and aesthetic worldview. The article also highlights the effectiveness of traditional pedagogical approaches rooted in oral professional music traditions, especially the ustoz–shogird (master–apprentice) system.